2010
DOI: 10.1073/pnas.1008382107
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of δ- and μ-opioid receptors in nociceptive sensory neurons

Abstract: Morphine-induced analgesia and antinociceptive tolerance are known to be modulated by interaction between δ-opioid receptors (DORs) and μ-opioid receptors (MORs) in the pain pathway. However, evidence for expression of DORs in nociceptive small-diameter neurons in dorsal root ganglia (DRG) and for coexistence of DORs with MORs and neuropeptides has recently been challenged. We now report, using in situ hybridization, single-cell PCR, and immunostaining, that DORs are widely expressed not only in large DRG neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
207
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(227 citation statements)
references
References 45 publications
17
207
3
Order By: Relevance
“…However the concentration of DAMGO used was high, potentially resulting in saturation of downstream second messenger pathways / effecter ion channels which may have prevented further inhibition. Despite their well-documented analgesic effects much remains to be understood regarding opioid receptor physiology in colonic extrinsic sensory afferents, with the potential for heteromeric complexes of opioid receptors to activate multiple G-protein receptor signaling pathways and potentially act on numerous effecter ion channels (Costantino et al, 2012;Wang et al, 2010). Further, mice lacking MOR have been shown to be more susceptible to TNBS induced colonic inflammation, indicating MOR activation may also have prominent effects on the immune system (Philippe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However the concentration of DAMGO used was high, potentially resulting in saturation of downstream second messenger pathways / effecter ion channels which may have prevented further inhibition. Despite their well-documented analgesic effects much remains to be understood regarding opioid receptor physiology in colonic extrinsic sensory afferents, with the potential for heteromeric complexes of opioid receptors to activate multiple G-protein receptor signaling pathways and potentially act on numerous effecter ion channels (Costantino et al, 2012;Wang et al, 2010). Further, mice lacking MOR have been shown to be more susceptible to TNBS induced colonic inflammation, indicating MOR activation may also have prominent effects on the immune system (Philippe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The rightward shift in the SNC80 dose−response curve in both μ-KO and δ-KO mice demonstrates that both μ-and δ-opioid receptor protomers in the heteromeric complex contribute to the antinociceptive activity of SNC80 in wild-type mice. This result is consistent with prior studies showing that SNC80-induced antinociception possesses both δ-and μ-opioid receptor-mediated 21,22 components.…”
mentioning
confidence: 95%
“…15 Additionally, in vitro studies on the effects of SNC80 on opioid receptors suggested the involvement of μ-opioid receptors on the activity of SNC80. These included the finding that colocalized μ-and δ-opioid receptors in large and small dorsal root ganglion (DRG) neurons 16 are cointernalized into the same subcellular compartment for lysosomal degradation upon treatment with SNC80. 17 These reports point to the involvement of both μ-and δ-opioid receptors in the activity of SNC80.…”
mentioning
confidence: 99%
“…Double immunofluorescence staining showed that DORs were present in SP-and CGRP-positive LDCVs in small DRG neurons in mice ( Figure 2A and Supplementary information, Figure S2A). This immunostaining pattern, which was shown with antibodies against DOR1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] , was abolished by the deletion of Oprd1 exon 1 in mice (Supplementary information, Figure S2A). Furthermore, β2 AR, G αi2 , PLCβ2, VGCC α2δ1 and P2X purinoceptor 2 (P2X 2 ) were present in SP-positive LDCVs in small DRG neurons (Figure 2A).…”
Section: Ldcv Localization Of Gpcrs Signaling Molecules and Ion Chanmentioning
confidence: 99%